Chrissie’s Death: orchestral performance and filmic narrative - Nogueira , Lisandro; Henrique Costa , Carlos; Batista Parente, Leonel (Seven Editora, 2023)
The purpose of this article is to conduct a discussion between orchestral music and itsparticipation in film narrative. In order to understand how the orchestral performance contributes to the construction of the narrative of a film, we made a cut of the scene Chrissie’sDeath, the opening scene of the film Jaws, by Esteven Spielberg. Chrissie’s Death was selected as the object of analysis because it is the scene in which the first shark attack occurs and, consequently, the first orchestral performance in the film Jaws. For the reading of the scene, carried out by means of analysis, we used as theoretical support the concept of Performance Intensity by Richard Schechner (2011), paired with the Functions of Music in audiovisual narrative, listed by Jiménez (1993). As a result, taking into account the Functions of Music in Audiovisual Narrative, it was possible to understand that the way the orchestra performs can assist in the construction of the narrative unity of the Chrissie’s Death scene. DOI: 10.56238/pacfdnsv1-046